"Counting One's Allies": The Mobilization of Demography, Population, and Family Planning in East Asia, Late 1920s–Present. Issue 4 (1st December 2016) - DiMoia, John P.
Abstract : This article interrogates the category "Cold War family planning" for the East Asian context (1945–1991), arguing that the category remains highly relevant while also reflecting a much longer regional history of demography and population studies. In this sense, the category is both useful and insufficient, especially if we fail to examine a revised periodization and a constructed nature for the category. If the category as constructed has its origins in a highly charged, ideological binary following the close of World War II and the fracture of colonialism, this reduced version of the narrative prioritizes the role of external partners, funding and grant agencies, and the attempt by powerful nations to reconstitute their relations with postcolonial nations through developmental aid. In turn, the longer version of the story emphasizes actors on the ground, the role of registration and demographic practice, and parties who strategically used the arrival of external actors to mobilize their own agendas. Cold War family planning thus represents a dynamic, interactive story, one in which multiple sets of partners with distinct agendas were able to work together. Building from this more complicated version, the final section of the article turns to the role of postwar Japan and Asian developmentalism, noting that family planning activities became a core part of the aid offered by emerging donor nations by the 1970s. Many Southeast Asian nations today encounter not just colonial history but also the reconfigured version of an earlier paternalism made available through their Asian partners.